Proceedings Frontiers in Education 35th Annual Conference
DOI: 10.1109/fie.2005.1612013
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study on Research in Engineering Education: Designing, Testing, and Administering the PACES-2 Survey on Academic Integrity

Abstract: Abstract-Most engineering educators excel at planning and conducting technical research in their field, but few are proficient doing this for a project in engineering education. Recently, however, there has been increased emphasis on conducting rigorous research in engineering education. This paper provides practical advice for planning and conducting such research. The authors use their long term project to predict academic dishonesty in engineering college students as a case study representing one approach t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…We followed this pilot testing with a test-retest protocol to establish the temporal stability of instrument items. The final phase of the study involved the full administration of the PACES-2 and DIT-2 survey instruments during several sessions (Finelli, Szwalek, Harding & Carpenter;.…”
Section: Research Instrumentsmentioning
confidence: 99%
“…We followed this pilot testing with a test-retest protocol to establish the temporal stability of instrument items. The final phase of the study involved the full administration of the PACES-2 and DIT-2 survey instruments during several sessions (Finelli, Szwalek, Harding & Carpenter;.…”
Section: Research Instrumentsmentioning
confidence: 99%
“…The final phase of the study involved the full administration of the PACES-2 and DIT-2 survey instruments to the study populations at all three schools. A total of 1600 randomly selected students from the three institutions were recruited to participate in the final phase of the study -800 from School A, and 400 each from Schools B and C. A number of approaches were used to increase response rate as described elsewhere (Finelli et al, 2005). Response rate varied by institution -27.9% for School A, 52.0% for School B, and 24.0% for School C. All instruments and methods described here were reviewed and approved by a behavioral sciences institutional review board.…”
Section: Instruments and Variablesmentioning
confidence: 99%
“…Additional contextual influences could further increase the model's ability to predict behavior. More information about the PACES-2 Study, including detailed statistics and results, can be found in other reports published by the E 3 Team 20,29,30,39 .…”
Section: Resultsmentioning
confidence: 99%